(untitled) - Kumada, Kyoichi (Tokyo, 1987)
In this book, humic acids are classified into A, B, Rp and P types, based on their optical properties. The elementary composition and other chemical properties of humic acid types are shown to be regularly different from each other. A new method for humus composition analysis applied to various kinds of soils in Japan and several other countries indicates that the diversity of humus compositions of soils is systematically understandable.
Keywords: Humus,Soils,Đất,Đất mùn; Humic acid content,Phân hủy mùn cưa